Extremely Large Mental Foramina in a Rare Case of Oral Hemangiolymphangioma - Ghazizadeh Ahsaie, Mitra; Iranparvar Alamdari, Mina; Mohammadpour, Maoud (Journal of Dental School, 2023)
Objectives Hemangiolymphangiomas (HLAs) are rare vascular malformations of lymphatic and blood vessels. These lesions commonly occur in the head and neck regions. In this paper, we describe a rare case of HLA, with significant effects on the mandibular bone and neurovascular canals. Case A 28-year-old patient with a history of head and neck HLA was referred to an oral and maxillofacial surgeon for dental implant placement. The results of radiographic analysis and cone-beam computed tomography (CBCT) indicated the mandibular bone enlargement, sclerosis, and bone remodeling. The inferior alveolar nerve canal (IANC) and mental foramen were markedly enlarged on both sides. Additionally, multiple soft tissue calcifications were present. The patient was referred to the oral and maxillofacial surgery (OMFS) department for further dental treatment. Conclusion Patients with maxillofacial vascular malformations require careful radiographic and imaging assessments before any surgical intervention, especially implant placement. Enlargement of neurovascular canals, especially IAN and mental foramen, along with the presence of sclerotic bone, should be considered as important findings, as they may significantly influence the surgical outcomes.